ANALYSIS OF PREGNANCY INTENSION RISK FACTORS IN INDONESIA WITH DEMOGRAPHIC HEALTH SURVEY (DHS) IN 2017 - Nida Luthfina (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
The pregnancy intention can be divided into two, namely the desired pregnancy and unwanted pregnancy/Kehamilan Tidak Diinginkan (KTD). Unwanted pregnancy can cause negative impacts on the mother, such as not carrying out antenatal care (ANC) and abortion. Besides, babies born from KTD are more at risk of experiencing low birth weight and not getting breast milk/Air Susu Ibu (ASI) from their mothers. Therefore, the risk factors of pregnancy intention need to be known to prevent the incidence of KTD in Indonesia. This study analyzes the risk factors for pregnancy intention in Indonesia, such as maternal age, parity, sex of the baby born, mother's work status, education level, type of area of residence, family economy, and history of contraceptive use or family planning/Keluarga Berencana (KB). The research design was cross-sectional with analysis using logistic regression statistical tests. This study used secondary data from the 2017 Demographic Health Survey (DHS) with 14,778 subjects. The results of this analysis are the risk factors for pregnancy intention in Indonesia, namely the age of the mother (p-value = 0,000 and OR = 1.403), parity (p-value = 0,000 and OR = 2,860), the type of area of residence (p-value = 0,000 and OR = 1,518) and history of use of family planning (p-value = 0.000 and OR = 0.711). The risk of adverse events is greater in mothers aged <20 years and> 35 years, parity more than 3, residing in urban areas, and having a history of using family planning. There is no significant relationship between the sex of the baby, the mother's employment status, education level, and family economy on pregnancy intention.